Frío, silencio y espacio vacío en El alma de los peces, de Antonio Gómez Rufo - García D’atri, Ana (Revista de Filología Románica, 2008)
Nature is not only a threat: it also represents human emotions in every way. Nature, like human beings, has a soul, at least a literary one that, in the case of the novel "The soul of the fishes", by Gómez Rufo, is used as an universal metaphor about the badness, about the darker side of human nature.